Long Term changes in Africa’s Rift Valley: impacts on biodiversity and ecosystems. - Chadri, Foreward. E.; Plumptre, Preface. A.J. (publication at: https://www.researchgate.net/publication/21646, 2014)
In 2000, MacArthur Foundation identified the Albertine Rift as an area of global importance for biodiversity conservation and it became a focal region for our Conservation and Sustainable Development program. We supported the creation of a common vision for conservation in the Albertine Rift through a process involving NGOs, protected area authorities, national universities and other stakeholders. In April 2003, we brought together key players who established key conservation objectives, defined the boundaries of the region, and identified six smaller landscape units for sub-regional planning. This plan has informed all our subsequent work in the region. An important recommendation in the plan was that a collaborative and standardized ecological monitoring framework was needed to gather information for all stakeholders interested in biodiversity conservation and sustainable development in the region. There are several long-term ecological monitoring programs in the Albertine Rift, including some that are more than 50 years old, but most of these programs do not monitor or share information across sites. The recommendation was echoed by the Wildlife Conservation Society in 2009 in a study of how climate change was affecting the biodiversity of the Albertine Rift; WCS found a scarcity of detailed, modern climate information for the region to work from. Despite Africa’s rich biodiversity and the importance of its ecosystem services, it has relatively few collaborative, network-based studies that examine the ecological impacts of climate change. This book marks the beginning of just such collaboration. It covers ecological information that spans across five countries in the Albertine Rift region, reflects over 50 years of research, and includes contributions from 65 researchers who represent 44 organizations at work in 11 sites. It provides invaluable information about past and current trends in the status of species, ecosystems and associated threats, as well as recommendations for interventions. This kind of ecological monitoring is crucial. It helps us understand the breadth and impact of ecological change, and regional and global drivers for the change; and allows us to respond more proactively to threats and opportunities for conservation and sustainable development.
Field Report
Keywords: Ecological factors; chimpanzees; Gombe National Park